2020
DOI: 10.1186/s13063-019-4036-6
|View full text |Cite
|
Sign up to set email alerts
|

A study protocol for a randomised trial of adjunct computerised memory specificity training (c-MeST) for major depression in youth: targeting cognitive mechanisms to enhance usual care outcomes in mental health settings

Abstract: Background: Youth depression is highly prevalent and is related to impairments in academic, social and behavioural functioning. Evidence-based treatments are available, but many young people do not respond or sufficiently recover with first-line options, and a significant proportion experience relapse. Consequently, there is clear scope to enhance intervention in this critical period of early-onset depression. Memory specificity training (MeST) is a low-intensity intervention for depression that targets reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
(54 reference statements)
0
5
1
Order By: Relevance
“…Future research might also incorporate c-MeST into other interventions. A study examining c-MeST as an adjunct to other treatments for depression is currently underway (Hallford et al, 2020). Integrating c-MeST into treatments that already target autobiographical memory, such as reminiscence therapies, might provide further enhancement of change processes (e.g., Kleijn et al, 2018; also see Pinquart & Forstmeier, 2012).…”
Section: Limitationsmentioning
confidence: 99%
“…Future research might also incorporate c-MeST into other interventions. A study examining c-MeST as an adjunct to other treatments for depression is currently underway (Hallford et al, 2020). Integrating c-MeST into treatments that already target autobiographical memory, such as reminiscence therapies, might provide further enhancement of change processes (e.g., Kleijn et al, 2018; also see Pinquart & Forstmeier, 2012).…”
Section: Limitationsmentioning
confidence: 99%
“…The sample of youth also completed the measures as part of a questionnaire in a repeated measures study, separate from that used in Study 1 (Hallford, Carmichael, et al, 2020). Recruitment for that study was still underway at the time of writing.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Recently, computerized MeST (c-MeST) was developed based on MeST, 20,21 and several studies have demonstrated its effectiveness on depression. 22 However, c-MeST is a web-based program that optimizes on a laptop or desktop. 23 Given that the number of older adults who can use smartphones is greater than the number of older adults who can use computers, the accessibility of video calls that can be made on mobile phones is higher than that of web-based programs for older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, computerized MeST (c‐MeST) was developed based on MeST, 20,21 and several studies have demonstrated its effectiveness on depression 22 . However, c‐MeST is a web‐based program that optimizes on a laptop or desktop 23 .…”
Section: Introductionmentioning
confidence: 99%